0706 Impact of Behavioral Insomnia Treatment on Post-Menopausal Female Sexual Functioning. (27th April 2018) - Tonnu, C V; Cheng, P; Kalmbach, D; Fellman-Couture, C; Tallent, G; Arnedt, J; Singh, M; Drake, C
Abstract: Introduction: Sexual difficulties are commonly reported in post-menopausal women, and can be worsened by insomnia. Although highly prevalent, insomnia can be effectively treated in post-menopausal women, but few studies have examined the impact of insomnia treatments on sexual functioning. This study examined how self-reported sexual functioning was impacted by two forms of behavioral intervention for insomnia compared to an attention control. Methods: 148 women who showed menopause-related insomnia were randomized into three conditions: Cognitive Behavioral Therapy for Insomnia (CBT-I; N=50), Sleep Restriction Therapy (SRT; N=49), and an Information-Control condition (IC; N=49). Insomnia was diagnosed using DSM-5 criteria. Sexual functioning was measured using the Female Sexual Functioning Index (FSFI) at baseline, post-treatment, and at 6-month follow up. Results: No group differences were found at baseline across all sexual functioning subscales. Independent sample t-tests indicated that total sexual functioning at post-treatment was significantly higher for CBT-I compared to IC (p=0.05), but not compared to SRT. Further analysis revealed that this effect was most prominent in the lubrication subscale, specifically between CBT-I and IC at post-treatment (p=0.02). Additionally, the pain subscale revealed a marginally significant difference at post-treatment (p=0.06) between CBT-I and IC. However, improvements in these subscales were not sustained at follow-up. No significant differences were found between groups for the remaining subscales (desire, arousal, satisfaction, and orgasm). An additional sub-analysis examining sexual activity found that of those who indicated not sexually active at baseline, 50% of those in the CBT-I condition became sexually active at post-treatment, compared to 12.5% and 25% of SRT and IC recipients respectively. At follow-up, sexual activity was 27.3%, 25%, and 20% for CBT-I, SRT, and IC respectively. Conclusion: While both CBT-I and SRT reduce insomnia in post-menopausal women, CBT-I may suggest additional benefits for sexual functioning whereas SRT may not. However, these gains only appear acutely, as they were not maintained at 6-month follow-up. Future research should explore what factors unique to CBT-I and not SRT may explain an increase in sexual functioning, and how these increases may be maintained over time. Support (If Any): MENO:R01NR013959.